Deep new: The shifting narratives of artificial intelligence from Deep Blue to AlphaGo. (August 2019) - Bory, Paolo
The article compares two key events that marked the narratives around the emergence of artificial intelligence (AI) in two different time frames: the game series between the Russian world champion Garry Kasparov and the IBM supercomputer Deep Blue held in New York in 1997, and the Go game series between the South Korean champion Lee Sedol and DeepMind's AI AlphaGo held in Seoul in 2016. Relying on a corpus of primary and secondary sources such as newspapers and specialized magazines, biographic books, the live broadcasts and the main documentaries reporting the challenges, the article investigates the way in which IBM and Google DeepMind used the human–machine competition to narrate the emergence of a new, deeper, form of AI. On the one hand, the Kasparov–Deep Blue match was presented by broadcasting media and IBM itself as a conflictual and competitive form of struggle between human kind and a hardware-based, obscure and humanlike player. While on the other hand, the social and symbolic message promoted by DeepMind and the media conveyed a cooperative and fruitful interaction with a new software-based, transparent and un-humanlike form of AI. The analysis of the case studies reveals how AI companies mix narrative tropes, gaming and spectacle in order to promote the newness and the main features of their products. In particular, recent narratives of AI based on human feelings and values such as beauty and trust can shape the way in which the presence of intelligent systems is accepted and integrated in everyday life.